Arte, ludicidade e orientação de visitas em museus e espaços culturais com crianças de Ensino Fundamental – EF – Ciclo I - Santi, Mariana Priscila de [UNESP]; Kobayashi, Maria do Carmo Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this ongoing presentation for playful material creation aimed to the cultural mediation with children cycle I, EF create, in museums and cultural spaces. The research will result in guidelines to assist teachers and cultural mediators in the organization of visits for children. They will address issues related to the emergence, social, cultural, recreational and educational function of these spaces for the development of aesthetic perception. Museums were created by curiosity and man's desire to preserve, collect and learn more about objects that are rare, exotic, which have emotional significance, artistic and historical. To familiarize with the way in which children learn through play, it is one of the ways to captivate them to learn about the art and sensitivity. The book-object is the material of choice to meet the purpose of this research. This choice was for trying to support a hybrid that can house toy, game, image and text at the same time and that can assist adults and children in cultural visits in privileged spaces of learning, which, however little visited by the child audience.

Apresenta-se nessa comunicação a pesquisa, em andamento, para a criação de material lúdico voltado a mediação cultural com crianças de ciclo I, EF, em museus e espaços culturais. A pesquisa resultará em orientações para auxiliar professores e mediadores culturais na organização de visitas para crianças. Serão abordadas questões relativas ao surgimento, a função social, cultural, lúdica e educacional desses espaços, para o desenvolvimento da percepção estética. Os museus surgiram pela curiosidade e pelo desejo do homem de preservar, colecionar e conhecer melhor objetos que são raros, exóticos, que tem importância afetiva, artística e histórica. Conhecer bem a maneira com a qual as crianças aprendem por meio do lúdico, é uma das maneiras de cativá-las a aprenderem sobre a arte e a sensibilidade. O livro-objeto é o material escolhido para atender a finalidade desta pesquisa. Essa escolha se deu por tratar de um suporte híbrido que pode abrigar brinquedo, jogo, imagem e texto ao mesmo tempo e que poderá auxiliar adultos e criança nas visitas culturais em espaços privilegiados de aprendizagem, que, entretanto pouco visitados pelo publico infantil.
Keywords: Cultural mediation; Childhood; Educational practice; Mediação cultural; Infância; Prática educativa